Hogyan tovább? Magyar almatermesztés a XXI. században: WHAT'S NEXT? APPLE GROWING IN THE XXI. CENTURY - Szűcs, Diána (Közép-Európai Közlemények, 2021)
Agriculture is a special industry with a lot of external influences that sometimes occur unexpectedly, so full rationalization is almost impossible. Weather is unpredictable, but can be adapted to. The volume of high processed products needs to be increased, while the lower value-added products and low processed products dominate in the Hungarian agrarian export. The problem with precision farming is that not all farmers can afford to use technology. The machines are expensive and require great economies of scale to use them. On the other hand, European agriculture consists of small or very small farms, which are often unable to provide viable income to farmers. The year of 2018 has more and more highlighted the serious problems which are faced by apple farmers in Szabolcs. Buyers suppressed the purchase price of industrial apples, which the producers considered too low, because they would not have covered even the cost price. Negotiations have been conducted and demonstrated, but instantaneous fire-fighting is not an option. What processions led to the autumn apple crisis? In the modern market economy, the focus of the production process is on the farmer who manages his own or rented land, relying heavily on the family's workforce. The main problem with the position of the individual farmer is that his market position is very weak in relation to other market participants and that he is unable to influence it or the price through his market position. The paper introduces the past transformation of the sector, the possible directions for farmers' organization and development, which are absolutely necessary to lay the foundations for the way out.